La situación sociolingüística de la lengua creole de San Andrés Isla: el caso de San Luis - Moya, Deyanira Sindy (Colombian Applied Linguistics Journal, 2014)
This paperaims at describing the linguistic situation of a particular sector on San Andres Island, Colombia called San Luis. It illustrates the use of three different languages, their functions and the relationship between language and speakers’ identity based on the results of a sociolinguistic study developed in 2009 and 2010 in this local area. Surveys, participant observation, interviews and life stories were used to collect information on how much these languagesareseen as part of the ethnical identity of native inhabitants on the island. Results show that there is a continuous expansion of Spanish and a possible loss of English on the island which leads to a need ofan intercultural bilingual education in order to promote a better understanding among diverse cultural and linguistic groups.